Ketoksikan Beberapa Racun Hamama dan Piretroid Timan terhadap Hamama Lelabah Merah, Tetranychus urticae Koch Kompleks - Ibrahim, Yusof; Omar, Dzolkhifli; Othman, Adnan (1992)
The toxicity of four acaricides and five synthetic pyrethroids against red spider mite, Tetranychus urticae Koch complex, was evaluated in the laboratory using the slide-dip technique. Mortality was recorded at 48 h post treatment and data were subjected to probit analysis. Based on the LC50 values, the order of toxicity of the chemicals tested was as follows: amitraz > deltamethrin = cypermethrin (CymbushR ) = fenvalerate > cypermethrin (RipcordR) > permethrin > bromopropylate = chinomethionate > azocyclotin. The LC50 value for amitraz was 2.5 ppm while for chinomethionate it was 37.5 ppm. Repeated tests on the toxicity of the pyrethroids using leaf dip technique at the LC50 and LC95 values obtained earlier from the slide-dip technique revealed a lower level of mortality. The highest mortality obtained was 21.0% from fenvalerate treatment at the LC95 value. Thus test techniques were found to give different toxicity values on the red spider mite.